2023
DOI: 10.1302/0301-620x.105b6.bjj-2022-0921.r1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between exposure to noise and hearing loss in orthopaedics

Abstract: AimsIn the UK, the agricultural, military, and construction sectors have stringent rules about the use of hearing protection due to the risk of noise-induced hearing loss. Orthopaedic staff may also be at risk due to the use of power tools. The UK Health and Safety Executive (HSE) have clear standards as to what are deemed acceptable occupational levels of noise on A-weighted and C-weighted scales. The aims of this review were to assess the current evidence on the testing of exposure to noise in orthopaedic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A systematic review by Mistry et al analysed the evidence on the noise generated from orthopaedic operations and instruments and compared this with the 2003 European Commission Directive and 2005 UK HSE National Occupational Health guidelines [ 19 ]. As identified in our study, they concluded that safe levels of noise can be exceeded during orthopaedic operations.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Mistry et al analysed the evidence on the noise generated from orthopaedic operations and instruments and compared this with the 2003 European Commission Directive and 2005 UK HSE National Occupational Health guidelines [ 19 ]. As identified in our study, they concluded that safe levels of noise can be exceeded during orthopaedic operations.…”
Section: Discussionmentioning
confidence: 99%